Giant dumbbell-shaped prostatic cystadenoma presenting as pelvic and scrotal mass - Xiao Wei Zeng; Shao Xing Zhu; Yi Peng Xu; Lin Feng Zheng; Zong Ping Wang; Jin Chao Chen; Ying Jun Jiang (Journal of the Pakistan Medical Association, 2020)
Abstract This study reports the case of an elderly man with a large tumour of the pelvic cavity and scrotum which was once diagnosed as a prostate cyst. Imaging studies considered the source of the tumour to be prostate, and the tumour was ultimately diagnosed by confirmed tissue expression of prostate specific antigen (PSA) and prostate acid phosphatase (PSAP) after surgery. This is the first report about dumbbell-shaped prostatic cystadenoma with invasive growth and even urethral damage, but there was no evidence of clear malignancy. Early diagnosis and treatment are crucial in such kinds of diseases. Keywords: Prostatic cystadenoma, prostate specific antigen, pelvic mass, scrotal mass, Continuous...